Nigeria Economic Update, Fall 2019 : Jumpstarting Inclusive Growth - Unlocking the Productive Potential of Nigeria’s People and Resource Endowments - World Bank Group (Washington, DC: World Bank, 2019)
Nigeria continues its recovery from the 2016 recession, sustaining an estimated 2 percent growthrate in 2019. The collapse of global oil prices during 2014–16, combined with lower domestic oil production, led to a sudden slowdown in economic activity. Nigeria’s annual real GDP growth rate, which averaged 7 percent from 2000 to 2014, fell to 2.7 percent in 2015 and to -1.6 percent in 2016. Growth rebounded to 0.8 percent in 2017, 1.9 percent in 2018, and then plateaued at 2 percent in the first half of 2019, where it is expected to remain for the rest of the year. Services, particularly telecoms, remained the main driver of growth in 2019, although trade started contracting amidst increasing use of policy measures aimed at import substitution. Agricultural growth picked up slightly but remains affected by insurgency in the Northeast region and ongoing farmer-herder conflicts. Industrial performance was mixed: growth in the oil sector remained stable, but manufacturing production slowed in a context of weaker power sector supply. Overall, the slow pace of recovery in 2019 is attributable to weak consumer demand and lower public and private investment. The annual headline inflation rate fell from a peak of 15.7 percent in 2016 to a projected 11.6 percent in 2019 but remains high and above the central bank’s target of 6–9 percent. The focus section of this report analyzes the evolution of productivity in Nigeria and identifies policies and institutions that can leverage productivity growth to accelerate Nigeria’s economic expansion and create new job opportunities. The analysis highlights four key priorities. First, ensuring policy transparency and predictability will be critical to reduce investment risk and promote growth outside the extractive industry. Second, investing in infrastructure, strengthening land tenure security, improving educational outcomes, and liberalizing the trade regime and enhancing trade and transport facilitation would help develop value chains and facilitate the efficient reallocation of factors of production, making Nigeria more cost-competitive. Third, reducing regulatory discretion would help attract foreign and domestic investment to the nonoil sector, encourage competition, and promote formalization.And fourth, improving access to finance could enable new firms to compete with incumbents and allow more productive firms to scale up their operations. Actions in these areas would lay the groundwork for Nigeria’s transition to a new economic model that more effectively utilizes its large, young population and abundant natural resources to support sustainable growth and poverty reduction.